Outcome after endovascular treatment for acute ischemic stroke by underlying etiology: Tertiary experience and meta-analysis - Ma, Chunlin; Cao, Wenbo; Huang, Yang; Tian, Qiuyue; Chen, Yanfei; Wang, Yabing; Chen, Jian; Gao, Peng; Dmytriw, Adam A.; Regenhardt, Robert W.; Chen, Fei; Ma, Qingfeng; et al. (Frontiers in Neurology, 2023)
Objective To investigate the effect of two major etiologies [intracranial atherosclerotic stenosis (ICAS) and cardioembolism (CE])] on outcomes of acute ischemic stroke (AIS) patients due to large vessel occlusion (LVO) after endovascular thrombectomy (EVT). Methods Anterior circulation AIS patients receiving EVT were retrospectively analyzed. Clinical and laboratory data were collected. Clinical outcomes including favorable outcome (90-day modified Rankin Scale 0–2), mortality, intracranial hemorrhage (ICH) and symptomatic ICH (sICH) were compared. A systematic review and meta-analysis was also performed. Results A total of 302 AIS patients were included and divided into the ICAS group (86 patients) and the CE group (216 patients). Patients in the ICAS group were younger (62[18.0] vs. 68[19.0] years, p < 0.001), more likely to have smoking (52.3% vs. 26.9%, p < 0.001) and drinking (52.3% vs. 23.1%, p < 0.001) history, and more frequently required rescue therapy (80.2% vs. 4.6%, p < 0.001) compared to the CE group. However, favorable outcome (aOR 0.722, 95%CI 0.372–1.402, p = 0.336) and mortality (aOR 1.522, 95%CI 0.606–3.831, p = 0.371) were not significantly different between the two groups before and after adjustment. The incidence of sICH and ICH were comparable between the two groups before and after adjustment. Systematic review and meta-analysis consisted of 8 eligible studies (7 previous studies and this current study), incorporating 552 ICAS patients and 1,402 CE patients. Favorable outcome was slightly more likely in the ICAS group compared to the CE group (54.2% vs. 46.3%, OR 1.40, 95%CI 1.00–1.96, I2 = 53.2%). Moreover, the ICAS group had a lower rate of mortality (14.3% vs. 22.2%, OR 0.63, 95%CI 0.46–0.87, I2 = 0.0%) and ICH (19.5% vs. 31.9%, OR 0.60, 95%CI 0.42–0.84, I2 = 0.0%) than the CE group, while the two groups were similar in sICH rate (5.9% vs. 6.7%, OR 0.94, 95%CI 0.55–1.60, I2 = 6.3%). Conclusion Etiology was not considered as an important factor in functional outcome, despite the differences in baseline characteristics and technical EVT approach. The current study of anterior circulation AIS-LVO patients supports that outcomes for those with ICAS are not significantly different from those with CE.